Muhammad Iqbal's Humanism: a Response to Religious-Sufistic and Secular Humanism - Hamdani, Basrir; Rasid, Rasid (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2024)
The nature of human being is not only the self who possesses ‘will to power’ or free will to determine the continuity of his life through fulfilling the biological needs, but also the self who is cosmological reflection of God, he is pervaded by divine values with active-participatory and creative manner. This article attempts to disclose a construction of Muhammad Iqbal’s idea on humanism based on spiritual-anthropological perspective in understanding human being. This idea of him on humanism constitutes a response and synthesis, as well, to two views; first, the view that only emphasizes on physical-biological aspect and denies spiritual-metaphysical aspect of human being as what maintained by modern Western humanism. Second, the view that is exceedingly fixated on spiritual-theocentric aspect and underestimates the anthropological-sociological aspects of human’s role as a living creature. The second one has afflicted mystical tradition in Islamic thought. By his philosophy of khūdī (ego), Iqbal proposes a holistic approach in understanding the reality of human being. He elaborates that human being is not only a creature that possesses privilege for actualizing his self-potential in material cases by means of creative actions but also a spiritual creature who has substance (human soul) which is everlastingly as the manifestation of Cosmic Creator who is Omni-Creative i.e., God as the Absolute Ego or the Perfect Self. This writing is proposed by means of analytical-descriptive method toward Iqbal’s philosophy in constructing the idea of humanism.